MANAJEMEN KEKAYAAN HNWI (High Net Worth Individual) BERBASIS SYARIAH - , Yanuar Partadiredja ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The thesis was a case study of High Net Worth Individual (HNWI) based on sharia (islamic law). The study aimed to provide recommendation for a busy client in wealth management specifically based on Islamic law. The recommendation provided was related to the three pillars of wealth management that was accepted by the client based on acceptable risk tolerance. Each of the pillars was analyzed and provided as a recommendation with two proposals of scenario. The result showed that scenario I and II would increase client wealth by IDR 18.203.375.412 in 2012 and IDR 36.429.078.762 in 2019. In 2026 when the client would be retired, the client wealth was expected to be IDR 103.259.700.061. In 2027 when the client would be in the first year of retirement the client wealth would be amounted for about IDR 124.060.338.246. The differences between scenario I and scenario II was on the year to year projected cash flow. In scenario I the surplus would be IDR 683.331.231 in 2011, IDR 1.307.244.030 in 2012, IDR 4.05.179.425 in 2019, IDR 8.016.279.662 in 2026 and IDR 19.138.936.085 in 2027 respectively. Meanwhile in scenario II the surplus was expected to be IDR 59.227.969 in 2011, IDR 59.714.777 in 2012, IDR 2.065.364.439 in 2019, IDR4.265.771.302 in 2026 and IDR 19.135.933.231 in 2027 respectively.